Literature and Film - Richardson, Robert (Indiana University Press, 1969)
A lucid and straightforward analysis that argues that film and literature are not the entirely different, antithetical disciplines they have been and are widely held to be. Mr. Richardson shows clearly the relationship of film to literature, outlining differences as well as similarities, and common goals as well as divergent aims appropriate to the two arts. He demonstrates how each form and its associated criticism is frequently able to illuminate and enliven the other. A film consciousness sharpens the reader's alertness to the visual and aural qualities that mark much great writing, and literary training, in turn, adds depth and perspective to appreciation of film. The author goes on to present some of the literary influences that have affected film during its development, and discusses the impact of film on modern literature. He concludes with an extended exploration of the relationship of film to poetry, suggesting that while the two forms use similar techniques, film has dealt more significantly with the problem of how to find a humane, noncoercive order in life.